Cytomorphometric Characteristics of Buccal Mucosal Cells in Behçet’s Disease Patients - Erol Aktunc; Zehra Safi Oz; Sibel Bektas; Cevdet Altinyazar; Rafet Koca; Serdar Bostan (Analytical Cellular Pathology, 2016)
Background. The aim of this study was to compare the cytomorphometric characteristics of the buccal cells of Behçet’s disease patients with those of healthy controls. Methods. This case-control study compared a group of 30 patients with Behçet’s disease with an age- and gender-matched control group of 30 healthy individuals. The buccal mucosal smears were stained using the Papanicolaou technique for cytomorphometric analyses. The nuclear and cytoplasmic areas were evaluated using digital image analysis; the ratio of nuclear to cytoplasmic areas and nuclear roundness are presented. Results. The nuclear and cytoplasmic areas of the BD patients’ cells were significantly smaller than those of the healthy controls’ cells, while the nucleus-to-cytoplasm ratio and neutrophil infiltration rate did not differ significantly between the groups. However, the nuclear area, cytoplasmic area, nucleus-to-cytoplasm ratio, and nuclear roundness factor were significantly higher in patients without aphthae. The neutrophil infiltration rate did not differ significantly in patients with or without aphthae. Conclusion. Behçet’s disease can produce cytomorphometric changes in buccal cells that are detectable by exfoliative cytology and cytomorphometric analysis techniques.